Green Inovasi dan Eko-Efisiensi Sebagai Strategi Keberlanjutan untuk Meningkatkan Kinerja Perusahaan di Sektor Konsumsi Primer - Listiya Ike Purnomo; Mega Kusuma Citra; Aina Al Pabrina (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2026)
The aim of this research is to gather empirical data regarding how green innovation and environmental efficiency influence the values of companies. This investigation centers on companies in the primary consumer goods sector that are listed on the Indonesia Stock Exchange from 2019 to 2023. Green innovation and environmental efficiency are regarded as components of a sustainable strategy capable of enhancing competitive advantages and drawing in investors. The research employs a quantitative method with purposive sampling. The analysis of the data was performed using a panel data regression technique through EVIEWS 12 software. The suitable regression model for addressing the hypothesis is the random effects model. The empirical findings indicate that green innovation does not influence firm value. Conversely, eco-efficiency has a notable positive impact on firm value. This result reinforces the idea that well-structured eco-efficiency practices, such as obtaining ISO 14001 certification, can serve as a favorable indicator for stakeholders. As a result, businesses should focus on bolstering their application of sustainability principles, particularly those related to resource efficiency, to enhance their value and appeal in investment circles.